Characteristics of human metapneumovirus infection in adults hospitalized for community-acquired influenza-like illness in France, 2012–2018: a retrospective observational study. (January 2021) - Loubet, P.; Mathieu, P.; Lenzi, N.; Galtier, F.; Lainé, F.; Lesieur, Z.; Vanhems, P.; Duval, X.; Postil, D.; Amour, S.; Rogez, S.; Lagathu, G.; et al.
Abstract: Objectives: To describe the prevalence, clinical features and complications of human metapneumovirus (hMPV) infections in a population of adults hospitalized with influenza-like illness (ILI). Methods: This was a retrospective, observational, multicenter cohort study using prospectively collected data from adult patients hospitalized during influenza virus circulation, for at least 24 h, for community-acquired ILI (with symptom onset <7 days). Data were collected from five French teaching hospitals over six consecutive winters (2012–2018). Respiratory viruses were identified by multiplex reverse transcription polymerase chain reaction (RT-PCR) on nasopharyngeal specimens. hMPV + patients were compared with hMPV– patients, influenza+ and respiratory syncytial virus (RSV)+ patients using multivariate logistic regressions. Primary outcome was the prevalence of hMPV in patients hospitalized for ILI. Results: Among the 3148 patients included (1449 (46%) women, 1988 (63%) aged 65 and over; 2508 (80%) with chronic disease), at least one respiratory virus was detected in 1604 (51%, 95% confidence interval (CI) 49–53), including 100 cases of hMPV (100/3148, 3% 95% CI 3–4), of which 10 (10%) were viral co-infection. In the hMPV + patients, mean length of stay was 7 days, 62% (56/90) developed a complication, 21% (14/68) were admitted to intensive care unit and 4% (4/90) died during hospitalization. In comparison with influenza + patients, hMPV + patients were more frequently >65 years old (adjusted odds ratio (aOR) = 3.3, 95% CI 1.9–6.3) and presented more acute heart failure during hospitalization (aOR = 1.8, 95% CI 1.0–2.9). Compared with RSV + patients, hMPV + patients had less cancer (aOR = 0.4, 95% CI 0.2–0.9) and were less likely to smoke (aOR = 0.5, 95% CI 0.2–0.9) but had similar outcomes, especially high rates of respiratory and cardiovascular complications. Conclusions: Adult hMPV infections mainly affect the elderly and patients with chronic conditions and are responsible for frequent cardiac and pulmonary complications similar to those of RSV infections. At-risk populations would benefit from the development of antivirals and vaccines targeting hMPV.